Factors Associated with Student Success in Online and Face-to-Face Delivery of Master of Science in Nursing Programs. - Cipher, Daisha J.; Urban, Regina W.; Mancini, Mary E. (Teaching & Learning in Nursing, 2019)
The purpose of this study was to identify academic and demographic characteristics of master's-level nursing students that predict successful program completion in face-to-face and online master's of science in nursing (MSN) programs. In addition, information was sought regarding online MSN students' retrospective appraisals of their program experience. This article reports survey results of 125 former students enrolled in 1 of 3 MSN programs: Family Nurse Practitioner, Nurse Educator, and Nursing Administration. Survey data collected included appraisals of quality, rigor, and preparation. The final survey sample included 125 respondents, of whom 92 were formerly enrolled in an online MSN program and 33 in an in-seat MSN program. Online and in-seat students did not significantly differ on any demographic or academic variables, nor the likelihood of graduation or discontinuation. Significant predictors of graduation included lower numbers of withdrawn classes and higher numbers of dropped classes. Program graduates reported moderate levels of confidence in their expanded career roles and moderate levels of certification examination preparation. Understanding the association between dropped classes, withdrawn classes, and persistence in MSN programs can assist academic program leaders to develop strategies to help their students to be successful. Identifying personal characteristics, situational variables, and academic factors that characterize persistence and predict graduation in MSN students is an area of study that requires further research.